Caracterización del suelo en plantaciones de Cedrelinga cateniformis Ducke “tornillo” de diferentes edades, Puerto Almendra Loreto-Peru, 2022 - Piña Gonzales, Jill Ilais (2023)
The study was carried out at the “Puerto Almendra Forestry Research and Education Center (CIEFOR), of the National University of the Peruvian Amazon (UNAP), located on the right bank of the Nanay River, 22 km south-west of the city. from Iquitos, (3° 49' 40" LS and 73° 22' 30" LO), at an approximate altitude of 122 masl, belongs to the “District of San Juan Bautista”, “Province of Maynas”, “Loreto Region” (UNAP, 2019, p.1). The objective was to characterize the soil of Cedrelinga cateniformis (Ducke) Ducke "tornillo" plantations of different ages. The importance of investigating critical soil levels is that these results enable us to make recommendations for corrective measures to improve soil quality. For this reason, the current state of the physical and chemical properties of the soil has been determined, which are similar to those of a natural forest, the pH is extremely acidic, the texture is sandy loam, the organic matter content is very low in the first years of the plantation and improves over the years, after 43 years of age they are similar to those of a natural forest, this occurs in the same way for Organic matter and Nitrogen and with respect to the Aluminum is very high reaching levels of toxicity. The homogeneous plantations of Cedrelinga cateniformis (Ducke) Ducke, do not improve the initial soil conditions, but they do not degrade it either. It has been possible to demonstrate that after 15 years of age the initial characteristics of the soil begin to regenerate and are recomposed with similar characteristics of the natural forest floor.